The Influence of Educators, Followers of John Dewey S Educational Thought, in the Chilean School System: Irma Salas, Amanda Labarca, and Dario Salas - Caiceo-Escudero, J (SAGE PUBLICATIONS INC, 2022)
Background/Context: This article discusses the influence and legacy of three Chilean educators in the country s schooling system during the first half of the 20th century. Focus of Study: Based on the changes that Dario Salas, Irma Salas, and Amanda Labarca promoted in the Latin American country, it explores how the ideas of their teacher John Dewey spread through Chile and endure to this day as part of the national curriculum. The article also debates the impact of cultural exchange between the United States and Chile since the influence in their country extended to social issues, such as the fight for gender equality, the creation of associations, and the improvement of civic engagement participation. Research Design: The study corresponded to historical research and was carried out in Chile based on the bibliographic background of the educators themselves and what the author himself has deepened about them for several years, that is, primary and secondary sources were investigated. Conclusion: The shifts towards secular education, the new experiential methodology, and the universal access to education were the main reforms achieved by the Chilean educators once they held leading positions in the education sector.